Routines in a European aquaculture company and the development of a Flavobacterium psychrophilum dose response pre-model in adult Rainbow Trout - Marques, Sara Raquel Silva (2016)
An internship in a European company dealing with aquaculture and biotechnology - AquaBioTech Group, Malta - was undertaken to complete the Master Degree of Science in Aquaculture of the School of Tourism and Maritime Technology of the Polytechnic Institute of Leiria. Biotechnology and aquaculture are two areas that have been synergistically used to contribute for the progress and improvement of fish production. The AquaBioTech Group is an example of a company able to integrate these areas to maximizing their services. Located in Mosta (Malta) the company operates in a sustainable way using Recirculation Aquaculture Systems (RAS) to maintain aquaculture species. In collaboration with several companies and institutions, the AquaBioTech Group is involved and supports the development of important international research projects. The present report focuses on two important parts of the internship performed during 6 months. Initially, it will cover the operation and constitution of the company, describing the routines and techniques acquired. Then, it will describe a pathology trial that forms the practical and scientific component of this report. Despite the limitation to describe some confidential assays, this trial consisted in the infection of Rainbow Trout (Oncorhynchus mykiss) with the bacterium Flavobacterium psychrophilum in order to evaluate the mortality rates over time. The internship served to solidify theoretical knowledge acquired during the academic training, develop professional skills and provide an understanding of jobs available on the market.